Key of life [videorecording (DVD)] - Uchida, Kenji, 1972-; Sakai, Masato, 1973-; Kagawa, Teruyuki, 1965-; Hirosue, Ryōko, 1980- (Film Movement series., 2013)
A failed actor switches identities with a stranger at a bath house--only to find himself filling the shoes of an elite assassin.